Engaging with Policy, Practice and Publics: Intersectionality and Impact - Hall, Sarah Marie; Hiveta, Ralitsa (Policy Press, 2020)
Available Open Access under CC-BY-NC licence. Engagement with non-academic groups and actors – such as policy-makers, industry, charities and activist groups, communities, and the public – in the co-production of knowledge and real-world impact is increasingly important in academic research. Drawing on empirical research, interdisciplinary methodologies, and broad international perspectives, this collection offers a critical examination of the liminal space of interactions between policy and research as spaces of difference and engagement, showing them to be far from apolitical. The authors consider what, and who, are present in these encounter spaces and examine how pre-existing perceptions about differences in social identity, positionality and knowledge can affect engagement, equity and research outcomes.